(untitled) (Acta Scientiarum. Agronomy, 2025)
Diversifying and rotating crops are of paramount importance in production systems; these practices aim to mitigate environmental risks and introduce new crops, thus supporting agricultural sustainability. Thus, the present study aimed to evaluate the productive performances of canola hybrids and to analyze the contribution of winter crops to the productivity of soybean grown in succession. Two experiments were conducted at two locations (Monsenhor Paulo and Luminárias, Minas Gerais, Brazil). The first experiment evaluated the performances of different canola hybrids: ALHT B4, Diamond, Hyola 433, Hyola 571 CL, Hyola 575 CL, and Nuola 300. The oil content (%), grain yield, and oil yield (kg ha-¹) of the plants were assessed. The second experiment evaluated the performances of soybean varieties grown after canola, white oats, and a fallow period. The Diamond and ALTH B4 hybrids exhibited high grain and oil productivity levels in Monsenhor Paulo, MG. The Hyola 575 CL hybrid excelled in Luminárias and had the highest levels of grain and oil productivity. In both locations, soybean yield and stand density were not influenced by the preceding crop (canola or oats) or fallow period. Among the other evaluated characteristics, only plant height was affected in Monsenhor Paulo, MG, and was greater after oat cultivation. In Luminárias, MG, there was an increase in the number of pods after oat cultivation.